The Islamic Declaration on Global climate change; An Ideological Discourse Analysis - Abdellah, Antar (Middle Eastern Journal of Research in Education and Social Sciences, 2020)
Purpose: The present study seeks to undertake a discourse analysis of the Islamic Declaration on Climate Change using Carvalho’s (2000) model of ideological discourse analysis. Approach/Methodology/Design: Two stages of the analysis were carried out: textual and contextual analysis. A corpus of 15 newspapers and media websites was developed out of 85 results attained by Factiva to undertake the contextual analysis. Findings: The results showed that the Islamic Declaration on climate change represents a critical moment in the history of caring for the environment in the Muslim world, that it represents mainstream Islam and common Muslim concern and not any single political or national agenda, that it bases its argument deeply on the Islamic faith represented in the scriptural texts, and that it has a potential influence both materially through policymakers and spiritually through changing peoples’ attitudes. Combined with other religious statements on climate change, the message of religious leaders is meant to reach areas modern science and governmental reports cannot reach alone. Practical Implications: While we attempted an ideological discourse analysis of the IDGCC in the present study, more studies are needed to analyze the influence of the IDGCC and other religion-inclined documents on people’s and governments’ actions to save the planet from the climate change crisis. Originality/value: The IDGCC was based on the Islamic faith to represent the ideology of mainstream Muslims and the Islamic perspective on the environment. Like the other religious statements, it relies heavily on scriptural references and interpretations.